Progress in Industrial Mathematics at ECMI 2006 - Bonilla, Luis L.; Moscoso, Miguel; Platero, Gloria; Vega, Jose M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
ECMI is synonymous with European Mathematics for Industry and organizes successful biannual conferences. The 14th European Conference for Mathematics in Industry held in Leganés (Madrid) focused on Aerospace, Information and Communications, Materials, Energy and Environment, Imaging, Biology and Biotechnology, Life Sciences, Finances and other topics including Education in Industrial Mathematics and web learning. Attendees came from all over the world. Overall, these proceedings give a lively overview of the importance of mathematical modeling, analysis and numerical methods when addressing and solving problems from today s real world applications. The accessible presentation of real problems from industry and finance, modeling, solutions via appropriate numerical and mathematical techniques are a source of fresh ideas and inspiration for mathematicians. Engineers and scientists in application fields may find useful ideas and techniques presented in familiar contexts that may help them to solve related problems in industry. Educators may find discussions of novel teaching experiences and examples from industrial contexts that could be useful devising curricula which include industrial mathematics and web learning.
Plenary Lectures -- Minisymposia -- Contributed Papers.
Keywords: Mathematics; Partial differential equations; Computer mathematics; Numerical analysis; Probabilities; Statistics; Mathematics; Computational Mathematics and Numerical Analysis; Partial Differential Equations; Computational Science and Engineering; Numerical Analysis; Probability Theory and Stochastic Processes; Statistics for Business/Economics/Mathematical Finance/Insurance.; Electronic books